Effects of L-DOPA/benserazide co-treatment on colonic excitatory cholinergic motility and enteric inflammation following dopaminergic nigrostriatal neurodegeneration. (1st September 2017) - Pellegrini, C.; Antonioli, L.; Colucci, R.; Tirotta, E.; Gentile, D.; Ippolito, C.; Segnani, C.; Levandis, G.; Cerri, S.; Blandini, F.; Barocelli, E.; Ballabeni, V.; et al.
Abstract: Introduction: The mainstay therapy for Parkinson's disease (PD) relies on L-3, 4-dihydroxyphenylalanine (L-DOPA) plus a DOPA-decarboxylase inhibitor. However, their effects on colonic dysmotility and inflammation observed in PD are undetermined. This study examined the effects of L-DOPA plus benserazide (BE) on colonic motility and inflammation in rats with central nigrostriatal dopaminergic denervation. Methods: Neurodegeneration was induced by 6-hydroxydopamine (6-OHDA) injection into the medial forebrain bundle (MFB). 6-OHDA animals were treated orally with L-DOPA/BE for 28 days, starting 28 days after 6-OHDA injection. At the end of treatment, in vivo colonic transit was evaluated by a radiologic assay. Electrically stimulated (ES) cholinergic contractions were recorded in vitro from colonic preparations, while acetylcholine release was measured in the incubation medium. Choline acetyltransferase (ChAT) and glial fibrillary acidic protein (GFAP) expression as well as eosinophil and mast cell density were examined in the colonic wall by immunohistochemistry. Colonic TNF and IL-1β levels were also assayed. Results: 6-OHDA animals displayed: 1) decrease in in vivo colonic transit; 2) impairment of ES-stimulated cholinergic contractions; 3) decreased acetylcholine release from myenteric nerves; 4) decrease in ChAT and increase in GFAP myenteric immunopositivity; 5) increase in eosinophil and mast cell density; 6) increase in TNF and IL-1β levels. Treatment with L-DOPA/BE elicited an improvement of in vivo and in vitro colonic motor activity, a normalization of acetylcholine release, ChAT immunopositivity, as well as pro-inflammatory cytokine patterns, ganglionic GFAP levels, eosinophil and mast cell density. Conclusion: Under dopaminergic nigrostriatal denervation, treatment with L-DOPA/BE ameliorated colonic motility through a normalization of myenteric cholinergic neurotransmission, along with an improvement of colonic inflammation. Highlights: L-DOPA effects on colonic dysfunctions in 6-OHDA rats are evaluated. L-DOPA administration restores colonic in vivo transit and in vitro contractility. L-DOPA treatment normalizes colonic cholinergic neurotransmission in 6-OHDA rats. L-DOPA improves colonic inflammation associated with central dopaminergic denervation.